Rising to the occasion: Diaspora remittances to Zimbabwe during the COVID-19 pandemic. (September 2022) - Mbiba, Beacon; Mupfumira, Daisy
Highlights: Zimbabwean diaspora in the UK remained largely employed during the COVID-19 pandemic and sent more remittances than in previous years. To send more money, individuals worked more hours, took out loans and changed their consumption behaviours. Remittances went to address urgent health, education, food and funeral needs - with the recipients overwhelmingly family and friends. New needs and 'one-off' recipients arose in Zimbabwe and South Africa whose large Zimbabwean diaspora has no welfare support. World Remit was the major money transfer operator used during COVID-19. Abstract: By early 2021, The World Bank was indicating that the massive COVID-19 induced declines in remittance flows it had predicted in the previous year had not materialised; actual declines were smaller and shorter term than expected. In some cases like that for Zimbabwe, there were significant increases. It argued that coronavirus pandemic lock down policies led to a shift from use of informal to formal recorded money transfer channels. However, given the diversity of contexts in source and receiving countries, there is need for continued localised investigations to understand the nature and development policy implications of these flows. Focusing on remittances sent by Zimbabweans settled in the UK (diaspora) during COVID-19 pandemic year, this paper draws on survey data to explore increases in the remittance flows, nature of, motivations for and purposes of remittances. Crucially it examines how the diaspora managed to increase the remittances when they were under immense financial pressure themselves. It confirms and contributes to understanding of the countercyclical nature of remittance flows.